PD-L1 Expression in Metaplastic Breast Carcinoma Using the PD-L1 SP142 Assay and Concordance Among PD-L1 Immunohistochemical Assays. (10th September 2021) - Grabenstetter, Anne; Jungbluth, Achim A.; Frosina, Denise; Hoda, Raza; Dos Anjos, Carlos H.; Patil, Sujata; Sevilimedu, Varadan; Weigelt, Britta; Reis-Filho, Jorge S.; Zhang, Hong; Traina, Tiffany; Robson, Mark E.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Immunotherapy for the treatment of programmed death-ligand 1 (PD-L1) positive locally advanced or metastatic triple negative breast cancer may benefit patients with metaplastic breast cancer (MpBC). Previous study of PD-L1 in MpBC scored tumor cells (TCs), different from Food and Drug Administration-approved scoring methods. We sought to define PD-L1 expression in MpBCs and to evaluate concordance of 3 PD-L1 assays. Primary, treatment naive MpBC treated at our Center from 1998 to 2019 were identified. PD-L1 expression was assessed using SP142, E1L3n, and 73-10. We evaluated PD-L1 expression on tumor infiltrating immune cells (IC) and also in TCs. For each assay, we scored PD-L1 expression using ≥1% IC expression according to the IMpassion130 trial criteria and using combined positive score (CPS) ≥10 according to the KEYNOTE-355 trial cutoff. A total of 42 MpBCs were identified. Most MpBC had PD-L1 positivity in ≥1% IC with all 3 assays (95%, 95%, 86%) in contrast to a maximum 71% with a CPS ≥10. PD-L1 IC expression was comparable between the SP142 and 73-10 assays and was lowest with E1L3n. PD-L1 TC expression was lowest using SP142. The overall concordance for IC scoring was 88% while 62% had concordant CPS. For each assay, the results of the 2 scoring algorithms were not interchangeable. The SP142 assay showed distinct expression patterns between IC (granular, dot-like) and TC (membranous) while 73-10 and E1L3n showed membranous and/or cytoplasmic expression in both IC and TC. Most MpBC in our cohort were positive for PD-L1 indicating eligibility for anti-PD-L1/programmed death-1 immunotherapy.